Atomic Force and Scanning Tunneling Microscopy of Ordered Ionic Liquid Wetting Layers from 110 K up to Room Temperature - Meusel, Manuel; Lexow, Matthias; Gezmis, Afra; Schötz, Simon; Wagner, Margareta; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (ACS nano, 2020)
Ionic liquids (ILs) are used as ultrathin films in many applications. We studied the nanoscale arrangement within the first layer of 1,3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C1C1Im] [Tf2N]) on Au(111) between 400 and 110 K in ultrahigh vacuum by scanning tunneling and noncontact atomic force microscopy with molecular resolution. Compared to earlier studies on similar ILs, a different behavior is observed, which we attribute to the small size and symmetrical shape of the cation: (a) In both AFM and STM only the anions are imaged; (b) only long-range-ordered but no amorphous phases are observed; (c) the hexagonal room-temperature phase melts 30-50 K above the IL's bulk melting point; (d) at 110 K, striped and hexagonal superstructures with two and three ion pairs per unit cell, respectively, are found. AFM turned out to be more stable at higher temperature, while STM revealed more details at low temperature.
CRIS-Team Scopus Importer:2020-08-28
Keywords: atomic force microscopy (AFM); Au(111); interface; ionic liquids (ILs); scanning tunneling microscopy (STM)